Faktor yang Mempengaruhi Minat Berkunjung Di Saung Bambu Pelangi Palembang - Decenvil, Celvin; Widagdo, Herry (MDP Student Conference, 2024)
The purpose of this study is to ascertain how amenities and attractions affect tourists' desire to visit Palembang's Saung Bambu Pelugu recreational area. Collecting data for this research, delivering questionnaires to 200 respondents. Utilising a purposive sampling technique and nonprobability sampling, SPSS 23 was employed for the sampling process. With a value of 0.000 < 0.05, the partial test findings indicated that facilities and attractions had a significant positive impact on interest in visiting. The results of the simultaneous test demonstrate that the attractions and amenities variables have a positive and significant impact on visitors' interest in visiting, with a F value of 102.056 and a significant value of 0.000.